17 Telemedicine in Patients with New Diagnosis of Heart Failure: From Clinical Research to Practice. (3rd June 2016) - Koulaouzidis, George; Mohee, Kevin; Barrett, David; Clark, Andrew
Abstract : Background: Heart failure (HF) is a complex clinical syndrome associated with high mortality and high rate of hospital readmissions. Telehealth (TH) is a promising strategy for improving HF outcomes but there is an urgent need to properly identify those patients in whom a TH approach would provide benefit. The purpose of this study was to determine if TH in patients with recently diagnosed HF and ejection fraction <45%, reduces the risk of re-admission from any cause or death from any cause. Methods: A retrospective study of 124 patients (78.2% male; 68.6 ± 12.6 years; 56.5% ischaemic aetiology) who underwent TH and 345 patients (68.5% male; 70.2 ± 10.7 years; 56.3% ischaemic aetiology) who underwent the usual-care (UC), between 2009–12. All patients had a recent diagnosis of HF, NHYA class II-III and ejection fraction < 45%. The TH group were assessed by body weight, blood pressure and heart rate on a daily basis using electronic devices with automatic transfer of measured data to an online database. The follow-up period was 12 months. Results: Death from any cause occurred in 8.1% of the TH group and 19% of the UC group, p = 0.002. Readmissions for any cause occurred in 63.7% of patients in the TH group and 62.5% of patients in the UC group, p = 0.8. The number of readmissions/patients was also similar in the two groups, 1.3 ± 1.7 in the TH group and 1.4 ± 1.7 in the UC group ( p = 0.9). A difference in the number of days in hospital was noted (8.1 ± 12.8 days in TH group and 9.5 ± 17.3 in UC group) but this was not statistically significant ( p = 0.4). There was significant difference in the days alive and away from the hospital in the two groups: 348.3 ± 5.5 days in the TH group and 329.9 ± 4.6 days in the UC group ( p = 0.008). Conclusions: In patients with a recent diagnosis of HF and reduced left ventricle systolic function, TH is associated with lower any-cause mortality. Furthermore TH has the potential to reduce number of days lost to hospitalisation and death.